2007
DOI: 10.1073/pnas.0610201104
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory neurons expressing transient receptor potential channel M5 (TRPM5) are involved in sensing semiochemicals

Abstract: Olfactory sensory neurons (OSNs) in the main olfactory epithelium respond to environmental odorants. Recent studies reveal that these OSNs also respond to semiochemicals such as pheromones and that main olfactory input modulates animal reproduction, but the transduction mechanism for these chemosignals is not fully understood. Previously, we determined that responses to putative pheromones in the main olfactory system were reduced but not eliminated in mice defective for the canonical cAMP transduction pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
157
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(169 citation statements)
references
References 50 publications
12
157
0
Order By: Relevance
“…Immunohistochemical data have shown that a subset of OSNs express TRPM5 (transient receptor potential channel M5) in the cilia (Kaske et al, 2007;Lin et al, 2007), and because CNG channel subunit A2 (CNGA2) is likely expressed in these cilia (Lin et al, 2007), these studies suggested, but did not prove, that TRPM5 could be activated by Ca 2ϩ influx through CNGA2 and be involved in pheromone transduction in the MOE. In addition, indirect evidence showing differential inhibition by pharmacological block of adenylyl cyclase III of the electroolfactogram (EOG) response of two putative pheromones 2-heptanaone and 2,5-dimethylpyrazine (DMP) versus two general odorants in controls but not in TRPM5 knockouts suggests that TRPM5 is involved in the transduction of pheromonal responses (Lin et al, 2007). Finally, recent work indicated that TRPM5 likely plays a role in mediating transduction for putative pheromones (Oshimoto et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemical data have shown that a subset of OSNs express TRPM5 (transient receptor potential channel M5) in the cilia (Kaske et al, 2007;Lin et al, 2007), and because CNG channel subunit A2 (CNGA2) is likely expressed in these cilia (Lin et al, 2007), these studies suggested, but did not prove, that TRPM5 could be activated by Ca 2ϩ influx through CNGA2 and be involved in pheromone transduction in the MOE. In addition, indirect evidence showing differential inhibition by pharmacological block of adenylyl cyclase III of the electroolfactogram (EOG) response of two putative pheromones 2-heptanaone and 2,5-dimethylpyrazine (DMP) versus two general odorants in controls but not in TRPM5 knockouts suggests that TRPM5 is involved in the transduction of pheromonal responses (Lin et al, 2007). Finally, recent work indicated that TRPM5 likely plays a role in mediating transduction for putative pheromones (Oshimoto et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In other loss of function studies, two key olfactory signal transduction proteins, the CNG channel and the G-protein G olf , were not required for generating synaptic specificity in the olfactory bulb (Belluscio et al, 1998;Lin et al, 2000). In the CNG-null animals, the interpretation that odorant-evoked activity does not influence axonal projections is somewhat muddled by the new finding that these mice are not completely anosmic, as initially reported (Brunet et al, 1996), and respond behaviorally (olfactometer), electrically (electro-oculography [EOG]), and cellularly (cfos activity) quite well to odorants that are classified as pheromone-like compounds (heptanone and 2,3-dimethylpyrazine [DMP]; Lin et al, 2006Lin et al, , 2007.In addition, recent genetic manipulation of stimulatory G protein has demonstrated that cAMP may regulate the expression of axon guidance molecules essential for OR-instructed axonal projections (Imai et al, 2006). Unfortunately, the behavioral phenotype of these mice, with a point mutation in the conserved tripeptide motif for coupling G proteins, was not reported, nor was any characterization of spontaneous spike generation.…”
mentioning
confidence: 99%
“…S1A). Although the MOS is thought to detect volatile odorants and the VNS is thought to be important for the detection of nonvolatile pheromones, evidence shows that the MOS is also involved in pheromone detection (1)(2)(3)(4)(5)(6)(7)(8). Surgical blocking of odorant access to the MOE, but not surgical ablation of the vomeronasal epithelium (VNE), eliminates preference to odors from the opposite sex in ferrets (9,10).…”
mentioning
confidence: 99%